Two ribosome recruitment sites direct multiple translation events within HIV1 Gag open reading frame. Issue 12 (26th April 2017) - Deforges, Jules; de Breyne, Sylvain; Ameur, Melissa; Ulryck, Nathalie; Chamond, Nathalie; Saaidi, Afaf; Ponty, Yann; Ohlmann, Theophile; Sargueil, Bruno
Abstract: In the late phase of the HIV virus cycle, the unspliced genomic RNA is exported to the cytoplasm for the necessary translation of the Gag and Gag-pol polyproteins. Three distinct translation initiation mechanisms ensuring Gag production have been described with little rationale for their multiplicity. The Gag-IRES has the singularity to be located within Gag ORF and to directly interact with ribosomal 40S. Aiming at elucidating the specificity and the relevance of this interaction, we probed HIV-1 Gag-IRES structure and developed an innovative integrative modelling strategy to take into account all the gathered information. We propose a novel Gag-IRES secondary structure strongly supported by all experimental data. We further demonstrate the presence of two regions within Gag-IRES that independently and directly interact with the ribosome. Importantly, these binding sites are functionally relevant to Gag translation both in vitro and ex vivo . This work provides insight into the Gag-IRES molecular mechanism and gives compelling evidence for its physiological importance. It allows us to propose original hypotheses about the IRES physiological role and conservation among primate lentiviruses.